2014
DOI: 10.3855/jidc.3747
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia caused by an Acinetobacter junii strain harboring class 1 integron and diverse DNA mobile elements

Abstract: Introduction: Infections caused by Acinetobacter junii are rarely reported. However, some outbreaks of septicemia in neonates and pediatric oncology patients, as well as meningitis, peritonitis, and ocular infection have been described. Since it is highly infrequent to find the molecular characterization of A. junii strains in literature, in this study we described the molecular characterization of A. junii isolates recovered from blood samples of a renal transplant patient. Methodology: The case was defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Um dos perfis de risco associado ao A. baumanni é o uso de antibióticos de amplo espectro, tornando dificultoso o tratamento bacteriano devido à resistência desenvolvida por esse microrganismo. As bactérias Gram-negativas apresentam estruturas diferenciadas das Gram-positivas, determinando qual tipo de resistência vai iniciar 25 .…”
Section: Resistência Antimicrobianaunclassified
“…Um dos perfis de risco associado ao A. baumanni é o uso de antibióticos de amplo espectro, tornando dificultoso o tratamento bacteriano devido à resistência desenvolvida por esse microrganismo. As bactérias Gram-negativas apresentam estruturas diferenciadas das Gram-positivas, determinando qual tipo de resistência vai iniciar 25 .…”
Section: Resistência Antimicrobianaunclassified
“…Affected individuals have multimorbidities and are usually hospitalized in the intensive care unit ( 1 , 2 ). Some other representatives of the genus, like Acinetobacter junii , are only sporadically associated with human infections ( 3 , 4 ). Recently, nosocomial infections produced by Acinetobacter spp.…”
Section: Announcementmentioning
confidence: 99%
“…The potency of new identification technologies including DNA sequencing, Multilocus sequence typing (MLST) and Matrix‐assisted laser desorption/ionization‐time‐of‐flight mass spectrometry (MALDI‐TOF MS) allows nowadays to achieve an accurate identification of microorganisms responsible of nosocomial infections . This has revealed that many species other than A. baumannii within the Acinetobacter genus can also cause nosocomial infections, being of particular relevance A. nosocomialis and A. pittii, other members of the A. baumannii ‐ calcoaceticus complex , as well as A. junii, A. lwoffii, A. ursingii and A. johnsonii .…”
Section: Light Sensing Is Distributed Within the Genus Acinetobactermentioning
confidence: 99%